Geometry of nonrelativistic string. (1st January 2023) - Moinuddin, Sk; Mukherjee, Pradip
Abstract: The nonrelativistic bosonic string theory in a curved manifold is formulated here using gauging of symmetry approach (Galilean Gauge theory). The corresponding model in flat space has some global symmetries. By localizing these symmetries as per Galilean Gauge theory, the action for the nonrelativistic string interacting with gravity is obtained. A canonical analysis of the model has been performed which demonstrate that the transformations of the basic field variables under gauge transformations in phase space are equivalent to the diffeomorphism parameters by an exact mapping. Thus complete consistency of our results from both Lagrangian and Hamiltonian procedures are established.